Thermal energy storage for CSP hybrid gas turbine systems: Dynamic modelling and experimental validation. (15th February 2018) - Mahmood, Mariam; Traverso, Alberto; Traverso, Alberto Nicola; Massardo, Aristide F.; Marsano, Davide; Cravero, Carlo
Highlights: Dynamic analysis of sensible type thermal energy storage by two different approaches. CFD model using ANSYS-FLUENT ® code and a reduced-order model using TRANSEO. Experimental validation of the simulation results from both models. Comparison of modelling capability and scope of each model. Estimation of total thermal losses from the storage vessel. Abstract: Integration of Thermal Energy Storage (TES) is one of the promising features of Concentrated Solar Power (CSP) technology which allows the Renewable Energy Sources (RES) to provide uninterrupted and dispatchable power supply, and thus facilitates the RES grid integration. Hybrid Solar Gas Turbine (HSGT) systems along with TES integration have gained great attention for the last decades. Numerical modelling and simulation tools are essential for the TES design optimization and analysis of its thermal behaviour during charging and discharging phases. This paper deals with the dynamic modelling and experimental validation of a TES at laboratory scale, which is part of the HSGT system. The TES is modelled with two different approaches: the CFD model using a commercial tool and a reduced-order model using the in-house transient simulation tool TRANSEO, which has been developed by Thermochemical Power Group (TPG) for the energy system dynamic analysis. The validation of both model results against the data obtained by the Authors through experimental investigation has highlighted that 2D discretization of the TES through the CFD model gives accurate representation of the thermal behaviour of the system, but it causes a significant computational expense. On the other side, 1D dynamic model reasonably predicts the time dependent thermal behaviour of TES, except some deviations from the experiments which are related to the simplified discretization scheme. However, due to its fast approach, the TRANSEO model can be effectively used to perform both TES initial design and sensitivity analysis, and also to develop or verify the control system at a later stage of HSGT system development.